2011
DOI: 10.1159/000324310
|View full text |Cite
|
Sign up to set email alerts
|

Are Serum Protein Biomarkers Derived from Proteomic Analysis Useful in Screening for Trisomy 21 at 11–13 Weeks?

Abstract: Objective: The aim of this study is to identify potential biomarkers for fetal trisomy 21 from previous publications using proteomic techniques and examine the potential value of such biomarkers in early screening for this aneuploidy. Methods: This was a case-control study of 25 pregnancies with fetal trisomy 21 and 50 euploid controls undergoing first-trimester screening for aneuploidies by a combination of maternal age, fetal nuchal translucency (NT) thickness and maternal serum free β-human chorionic gonado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 56 publications
1
17
0
1
Order By: Relevance
“…Recently, afamin was identified as a potential biomarker for trisomy 21 by proteomic comparative analysis of plasma from pregnant women [36]. However, this finding was not confirmed in a later study comparing 25 women pregnant with trisomy-affected babies and 50 euploid healthy pregnancies [36].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, afamin was identified as a potential biomarker for trisomy 21 by proteomic comparative analysis of plasma from pregnant women [36]. However, this finding was not confirmed in a later study comparing 25 women pregnant with trisomy-affected babies and 50 euploid healthy pregnancies [36].…”
Section: Discussionmentioning
confidence: 94%
“…The previously reported abundance of afamin in human follicle fluid suggests the importance of afamin for oocyte development, maturation and hence fertility in general, most likely due to its vitamin E-carrying property [6]. Recently, afamin was identified as a potential biomarker for trisomy 21 by proteomic comparative analysis of plasma from pregnant women [36]. However, this finding was not confirmed in a later study comparing 25 women pregnant with trisomy-affected babies and 50 euploid healthy pregnancies [36].…”
Section: Discussionmentioning
confidence: 96%
“…Among full autosomal trisomy, only trisomy 21, 18, and 13 are capable of postnatal survival and are susceptible to a spectrum of diseases including cancer . In the last two decades, several biochemical and biophysical traits have been identified that led to considerable improvement in the non‐invasive screening for such trisomies . Current practice relying on combined maternal serum testing using different markers, such as alphafetoprotein, β ‐human chorionic gonadotropin, and unconjugated oestriol yields a 69% detection rate, which can be increased to approximately 80–85% by adding use of ultrasound markers, such as thickened nuchal fold .…”
Section: Introductionmentioning
confidence: 99%
“…The current practice of using single protein biomarkers will most likely give way to the use of multiplexed biomarkers, as they promise better sensitivity and specificity . Use of proteomics platform to mine deep into the plasma proteome has resulted in the identification of several target candidate markers for Down syndrome (DS) . In silico approaches using data mining techniques have also been used to identify proteins other than those previously reported as well as associated with chromosome 21 .…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that levels of fetuin A in amniotic fluid might differ between pregnancies with DS and euploid pregnancies and that presence or absence of features in the DS group may potentially be associated with the metabolic actions of fetuin A. Fetuin A, which has been studied in maternal serum as a potential novel marker in prenatal diagnosis of trisomy 21 in the first trimester, has not been found to differ significantly in levels between euploid and aneuploid pregnancies [10]. The focus of our study is to elucidate a number of metabolic pathways in trisomy 21 rather than add new information to the already studied field of prenatal diagnosis.…”
Section: Introductionmentioning
confidence: 99%